ქართული ტიტულატურა ტაო-კლარჯეთის სამეფოს მმართველ ბაგრატიონთა დინასტიაში - ბახტაძე, მიხეილ (მერიდიანი, 2015)
The Bagrationi dynasty rulers of Tao-Klarjeti had both Georgian and Byzantiane titles. Presumably, Georgian titles existed in parallel to Byzantine titles and independent from them. The following Georgian titles have been fixed in the Bagrationi family: Mepet-Mepe (King of the Kings), Mepe (King), Kartvelta Mepe (King of the Kartvelians/Georgians), Eristavt-Eristavi (Duke of the Dukes), Eristavi (Duke) and Mampali (Lord). In reality of Tao-Klarjeti the title Mepe, perhaps, was honorable title from the beginning which could be used in relation to any Bagrationi. The title King of the Georgians emerged in 888. In our view, the emergence of this title, as well as that of Eristavt-Eristavi and Eristavi was clearly anti-Byzantine step. The reinforcement of the principality, which by itself meant weakening of Byzantine influence, necessarily required the introduction of Georgian titles in parallel with the Byzantine titles and accordingly, hierarchy. The question arises; why in 888. In our view, a certain role was played by the restoration of kingship in Armenia; the reactivation of kingdom of the Abkhasians (Western Georgia). The Kings of the Abkhasians had already made a statement on primacy in “Georgian space”. The struggle for supremacy demanded equal “status” with the rulers of Western Georgia. The following rulers had title King of the Georgians: Adarnase, son of David (888-923), David, son of Adarnase (923-937), Bagrat, son of Adarnase (937-945), Bagrat II Regueni (958-994), David Kuropalates (994-1001), Bagrat III (1001-1014). At the end of the 10th century the title of the King of the Kings emerges in the Bagrationis. As it is seen, this title was first received by Gurgen, son of Bagrat II Regueni. In Tao-Klarjeti Bagrationis four persons held the title of Mampali. Guaram, son of Ashot, Sumbat, son of Adarnase and his sons, Bagrat and David. Mampali was supposedly an honorary title which existed in the first and second generations of Ashot Kuropalates. Then it was abolished as unnecessary for the newly established Georgian hierarchical system. In our view there emerged two new titles instead of Mampali: Eristavt-Eristavi and Eristavi. Of Tao-Klarjeti Bagrationis the title of Eristavt-Eristavi was held by Ashot Kukhi, David, son of Adarnase, Gurgen the Great, Sumbat, son of David Mampali, Sumbat, son of Adarnase, Bagrat, son of Adarnase, David, son of Adarnase, Bagrat II, Sumbat, son of Bagrat II. Of Tao-Klarjeti Bagrationis the title of Eristavi was held by Gurgen, son of Bagrat Mampali and David, son of Adarnase.
GEORGIAN TITLES IN THE BAGRATIONI DYNASTY, RULERS OF TAO-KLARJETI
https://geohistory.humanities.tsu.ge/ge/procedings/83-shromebi/163-shromebi-9.html
Keywords: ქართველთა მეფე; მეფეთა-მეფე; აშოტ კურაპალატი; ტიტულატურა